Analisis Struktural Perdagangan di Indonesia: Pendekatan Bayesian VAR - Fadlilah, Annastia Abqiatul; Kurniawan, Mahrus Lutfi Adi (Cendekia Niaga, 2024)
This research aims to determine the response of central government expenditure, government debt, government capital expenditure, population growth to international trade. The dependent variable in this research is the international trade variable and the independent variables include government debt, central government spending, government capital spending and population growth. The data in this research includes time series data in the form of percentages from 1971-2020 which were analyzed using the VAR (Vector Autoregressive) method. The results of this research are that all variables have a significant and positive response to international trade shocks. Based on the variance decomposition test, all variables contribute to international trade and have an increasing contribution until the final period. This is shown by the S.E value in period one of 12,242 and increasing in period ten of 27,282. Then the state debt variable has a high contribution to international trade and is continued with the government spending, capital learning and population growth variables.